Text Messaging May Engage and Benefit Adults with Type 2 Diabetes Regardless of Health Literacy Status - Erin M. Bergner; Lyndsay A. Nelson; Russell L. Rothman; Lindsay Mayberry (SLACK Incorporated, 2017)
Background: Technology-delivered interventions have the potential to improve diabetes self-care and glycemic control among adults with type 2 diabetes (T2D). However, patients who do not engage with interventions may not reap benefits, and there is little evidence on how engagement with mobile health interventions varies by health literacy status. Objective: This study explored how patients with limited health literacy engaged with and experienced Rapid Education/Encouragement and Communications for Health (REACH), a text messaging intervention designed to support the self-care adherence of disadvantaged patients with T2D. We recruited adults with T2D from federally qualified health centers and used mixed methods to examine (1) associations between users' health literacy status and their prior mobile phone use and their engagement with REACH and (2) similarities and differences in users' self-reported benefits by health literacy status. Methods: Participants (N = 55) completed a survey, including measures of health literacy and prior mobile phone use. For 2 weeks, participants experienced REACH, which included daily text messages promoting self-care and asking about medication adherence, and weekly text messages providing medication adherence feedback. After 2 weeks, participants completed a semi-structured telephone interview about their experiences. Key Results: Participants with limited health literacy were less likely to have used cell phones to access the Internet (48% vs. 90%, p = .001) or email (36% vs. 87%, p < .001), but equally as likely to have used text messaging and to respond to REACH text messages (p = .12 and p = .40, respectively) compared to participants with adequate health literacy. Participants responded to 93% of text messages on average and reported benefits of the intervention, including reminders and accountability, convenience and accessibility, and information and motivation. Participants with limited health literacy described a unique benefit of receiving social support from the intervention. Conclusions: Text messaging interventions may engage and benefit patients with T2D, regardless of health literacy status. Text messaging may have the potential to reduce T2D health disparities related to limited health literacy.